Dawn of a New Era: History of Uzbekistan's Higher Education System Transforms with Matrix Management - Shaturaev Jakhongir (Universitas Pendidikan Indonesia, 2023)
This research explores the impact of the transition to matrix management within history Uzbekistan's higher education system, marking a significant shift in its administrative and operational paradigm. The study posits that the adoption of matrix management will engender a range of positive outcomes. This approach uses a mixed-methods design with descriptive methods. Firstly, the author hypothesizes that the shift will improve operational efficiency through better resource allocation and interdepartmental collaboration. This is anticipated due to matrix management's inherently flexible structure, allowing for more dynamic resource utilization and encouraging cross-functional teamwork. This research suggests that this transformation will lead to heightened job satisfaction among faculty and staff. Matrix management, with its emphasis on open communication and collaborative decision-making, is expected to create a more engaged and motivated workforce. The results of this study could potentially inform other sectors in history Uzbekistan and other nations grappling with similar educational challenges, particularly those seeking to improve efficiency, innovation, and stakeholder satisfaction within their systems. This research underscores the significance of administrative and managerial strategies in transforming the higher education landscape, paving the way for future educational excellence.